Mitochondrial Dysfunction and Its Relationship with mTOR Signaling and Oxidative Damage in Autism Spectrum Disorders - Yui, Kunio; Sato, Atsushi; Imataka, George (Mini Reviews in Medicinal Chemistry, 2015)
Mitochondria are organelles that play a central role in processes related to cellular viability, such as energy production, cell growth, cell death via apoptosis, and metabolism of reactive oxygen species (ROS). We can observe behavioral abnormalities relevant to autism spectrum disorders (ASDs) and their recovery mediated by the mTOR inhibitor rapamycin in mouse models. In Tsc2+/- mice, the transcription of multiple genes involved in mTOR signaling is enhanced, suggesting a crucial role of dysregulated mTOR signaling in the ASD model. This review proposes that the mTOR inhibitor may be useful for the pharmacological treatment of ASD. This review offers novel insights into mitochondrial dysfunction and the related impaired glutathione synthesis and lower detoxification capacity. Firstly, children with ASD and concomitant mitochondrial dysfunction have been reported to manifest clinical symptoms similar to those of mitochondrial disorders, and it therefore shows that the clinical manifestations of ASD with a concomitant diagnosis of mitochondrial dysfunction are likely due to these mitochondrial disorders. Secondly, the adenosine triphosphate (ATP) production/oxygen consumption pathway may be a potential candidate for preventing mitochondrial dysfunction due to oxidative stress, and disruption of ATP synthesis alone may be related to impaired glutathione synthesis. Finally, a decrease in total antioxidant capacity may account for ASD children who show core social and behavioral impairments without neurological and somatic symptoms.
Keywords: mitochondrial dysfunction